Pengaruh Interval Waktu Pemberian Pupuk Organik Cair Berbahan Baku Keong Mas Terhadap Pertumbuhan dan Produksi Hijauan Pennisetum purpureum cv. Mott - Silvester Muga Sada; Bernadete Barek Koten; Bernadus Ndoen; Agustinus Paga; Paskalis Toe; Redempta Wea; Ariyanto Ariyanto (Jurnal Ilmiah Inovasi, 2018)
The research with aim to assessing the effect of giving  time interval of organic liquid fertilizer made golden snail aplle on growth and forage production Pennisetum purpureum cv. Mott, has been held for 3 months at the Kupang State Agricultural Polytechnic gardens forage at Oesao. The study was designed by Randomized Block Design, with 5 treatments and 5 block, which consists of the P0: without organic liquid fertilizer, P5: every 5 days, P7: every 7 days, P9: every 9 days , P11: every 11 days. The variables are number of shoots (number/ week), high gain (cm/ week), production of fresh weight (tons/ ha), dry matter production of forage (tons/ ha). Analysis of variance showed that the interval timing of organic liquid fertilizer made of snails  no significant  effect (P>0.05) to number of shoots, high gain,   fresh weight production of forage, and  dry matter production of forage. The average of number of shoots are 10.11/ week (P0: 10.46; P5: 11.35; P7: 10.41; P9: 9.39; P11: 8.94), the increase plant height 20.90 cm/ week (P0: 21.06; P5: 22.01; P7: 21.20; P9: 20.61; P11: 19.60), 53.32 tonnes / ha the fresh production of forage (P0: 53.62; P5: 57.71; P7: 49.39; P9: 55.18; P11: 50.71), 7.73 tonnes/ ha of dry matter of forage (P0: 7.72; P5: 8.80; P7: 7.17; P9: 7.68; P11: 7.26).  It was concluded that the growth and forage production of Pennisetum purpureum cv. Mott is not be effected of  effect of time interval of liquid organic fertilizer made from raw of golden snail.